Cardiac microvascular endothelial cells express a functional Ca 2+-sensing receptor - Berra Romani, Roberto (2008)
The mechanism whereby extracellular Ca2+ exerts the endothelium-dependent control of vascular tone is still unclear. In this study, we assessed whether cardiac microvascular endothelial cells (CMEC) express a functional extracellular Ca2+-sensing receptor (CaSR) using a variety of techniques. CaSR mRNA was detected using RT-PCR, and CaSR protein was identified by immunocytochemical analysis. In order to assess the functionality of the receptor, CMEC were loaded with the Ca2+-sensitive fluorochrome, Fura-2/AM. A number of CaSR agonists, such as spermine, Gd 3+, La3+ and neomycin, elicited a heterogeneous intracellular Ca2+ signal, which was abolished by disruption of inositol 1,4,5-trisphosphate (InsP3) signaling and by depletion of intracellular stores with cyclopiazonic acid. The inhibition of the Na +/Ca2+ exchanger upon substitution of extracellular Na+ unmasked the Ca2+ signal triggered by an increase in extracellular Ca2+ levels. Finally, aromatic amino acids, which function as allosteric activators of CaSR, potentiated the Ca2+ response to the CaSR agonist La3+. These data provide evidence that CMEC express CaSR, which is able to respond to physiological agonists by mobilizing Ca2+ from intracellular InsP3-sensitive stores.